Landslide susceptibility mapping and management in Western Serbia: an analysis of ANFIS- and SVM-based hybrid models - Elkhrachy, Ismail; Ranjan Yadav, Rajeev; Nouh Mabdeh, Ali; Nguyen Thanh, Phong; Spalevic, Velibor; Dudic, Branislav (Frontiers in Environmental Science, 2023)
Landslide susceptibility mapping (LSM) is essential for land-use planning, as it helps to identify areas at risk of landslides and enables effective prevention measures to be taken. Various statistical and machine learning (ML) models are used in LSM, including SVM and ANFIS, which have shown promising results. However, determining which model performs better remains a key challenge. To address this issue, this paper aims to compare six hybrid models constructed with two well-known and powerful ML models, namely SVM and ANFIS, and three meta-heuristic algorithms, namely Genetic Algorithm (GA), Differential Evolution (DE), and Cultural Algorithm (CA), for LSM in a case study in western Serbia. In the process of building the models, 359 landslide sites and 14 determinants were used. The accuracy of the models was evaluated using several indexes, including Root Mean-Squared Error (RMSE), coefficient of determination (R2), and Area under the Receiver Operating Characteristic Curve (AUROC). The modeling results showed that the SVM-GA model has the highest accuracy (AUROC= 0.78) in predicting landslide incidence, followed by the ANFIS-GA (AUROC= 0.775), SVM-CA (AUROC= 0.773), ANFIS-DE (AUROC= 0.771), SVM-DE (AUROC= 0.76), and ANFIS-CA (AUROC=0.65) models in validation phase. Therefore, the study suggested that SVM-based hybrid models are more accurate than ANFIS-based models for LSM, and thus, modelers may use SVM-based hybrid models for such applications. This study provides valuable insights into identifying the most appropriate and effective models for LSM, which can help to mitigate the risks associated with landslides and ensure sustainable land-use practices.